Vanadium (III) Oxide/Carbon Core/Shell Hybrids as an Anode for Lithium‐Ion Batteries. Issue 1 (7th December 2018) - Budak, Öznil; Srimuk, Pattarachai; Tolosa, Aura; Fleischmann, Simon; Lee, Juhan; Hieke, Stefan W.; Frank, Anna; Scheu, Christina; Presser, Volker
Abstract: We present a facile two‐step synthesis of vanadium (III) oxide/carbon core/shell hybrid material for application as lithium‐ion battery electrode. The first step is a thermal treatment of a mixture of vanadium carbide (VC) and NiCl2 ⋅ 6H2 O at 700 °C in an inert gas atmosphere. Elemental nickel obtained from decomposing NiCl2 ⋅ 6H2 O served as a catalyst to trigger the local formation of graphitic carbon. In a second step, residual nickel was removed by washing the material in aqueous HCl. By replacing NiCl2 ⋅ 6H2 O with anhydrous NiCl2, we obtained a hybrid material of vanadium carbide‐derived carbon and a vanadium carbide core. Material characterization revealed a needle‐like morphology of the rhombohedral V2 O3 along with two carbon species with a different degree of graphitic ordering. We varied the NiCl2 ⋅ 6H2 O‐to‐VC ratio, and the optimized material yielded a capacity of 110 mAh ⋅ g −1 at 2.5 A ⋅ g −1 which increased to 225 mAh ⋅ g −1 at 0.1 A ⋅ g −1 after 500 cycles in the potential range of 0.01‐3.00 V vs. Li/Li + . This enhanced performance is in stark contrast to the loss of lithium uptake capacity when using commercially available V2 O3 mixed with carbon black, where 93 % of the initial capacity was lost after 50 cycles. Abstract : Vanadium carbide and NiCl2 ⋅ 6H2 O react at 700 °C in an inert gas atmosphere by the formation of a V2 O3 /C core/shell hybrid material. Elemental nickel is a side‐product that improves the degree of ordering of carbon and can be removed easily by HCl washing. When tested as electrode for lithium‐ion batteries, the best resulting hybrid material yielded a capacity of 225 mAh g −1 at 0.1 A ⋅ g −1 after 500 charge/discharge cycles in the potential range of 0.01‐3.00 V vs. Li/Li + .